C1 Lateral Mass Screw Migration Causing a Delayed Unilateral Hypoglossal Nerve Lesion: A Case Report. Issue 1 (9th March 2016) - Hollern, Douglas; Shafi, Karim; Miller, Andrew; Woods, Barrett; Heller, Joshua; Vaccaro, Alexander
Abstract : Case: We present the case of a fifty-eight-year-old woman who was initially treated with a C1 to C7 anterior-posterior cervical decompression and fusion for an epidural abscess and returned two years postoperatively with four days of progressive dysphagia and tongue deviation. She was diagnosed with a unilateral hypoglossal nerve (cranial nerve XII) palsy secondary to compression from a C1 lateral mass screw. Conclusion: This is the first reported case that we are aware of describing a delayed cranial nerve palsy secondary to cutout and cephalad migration of a C1 lateral mass screw resulting in a neurologic deficit due to impingement on the hypoglossal nerve.